2014
DOI: 10.2139/ssrn.2493052
|View full text |Cite
|
Sign up to set email alerts
|

Douglass North's Theory of Institutions: Lessons for Law and Development

Abstract: This paper offers a critical overview and assessment of North's work on institutions and economic change, focusing on aspects of his work that are of interest to law and development scholars. It examines North's approach to institutions through his historical work focusing on his concept of credible commitment and his interpretation of the effect of the Glorious Revolution on property rights, focusing especially on the role he assigns to property rights in bringing about the Industrial Revolution. The paper al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 126 publications
0
12
0
1
Order By: Relevance
“…New institutional economics (NIE) examines the role of institutions in developed economies on economic growth (Faundez, 2016). As defined by Douglas North, an architect of NIE, institutions are the "rules of the game" in society that constrain human interaction (North, 1990).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…New institutional economics (NIE) examines the role of institutions in developed economies on economic growth (Faundez, 2016). As defined by Douglas North, an architect of NIE, institutions are the "rules of the game" in society that constrain human interaction (North, 1990).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Legal regulations set boundaries, even though multinational firms develop capabilities in dealing with institutions that are transferable (Carney et al, 2016). Limited transferability from institutions and capabilities displaying path dependency (e.g., Faundez, 2016) likely has an impact on choices for the speed of integration in cross-border acquisitions.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…A study by Changli and Xiaodong [29] showed that policy support can influence users' intentions to use balance treasure by directly influencing subjective norms. Policy and system are constraints that are artificially designed and shape people's interactions and exert important influence on personal beliefs, attitudes, and social behavior [30]. When making human genetic resource provision decisions, providers are not only affected by relatives and friends around them, but they are also affected by policies and institution.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…A study by Jun and Singh (1996) concluded that institutions do not have a substantial impact in promoting FDI. Besides, the Douglas North approach discusses the role of institutions in economic growth and investment (Faundez, 2016). According to North, institutions affect economic growth by increasing or decreasing transaction and production costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are three critical reasons for this, consisting of ownership advantage, internalisation advantage, and locational advantage. Based on Douglas North and Dunning's theoretical underpinnings, there seems to be a relationship between FDI and institutional stability (Faundez, 2016;Stoian and Filippaios, 2008). However, there is also the concern of crowding out domestic investment (Tekin, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%